ECONOMIC IMPACT OF SPECIAL AUTONOMY FUNDS ON REGIONAL DEVELOPMENT IN ACEH - Ahmad Kasyfi Ali (Gabungan Riset Edukasi dan Ekplorasi Teori (GREET), 2025)
This study examines the economic impact of Special Autonomy Funds (SAF) on regional development in Aceh, Indonesia, a post-conflict province with unique political and social dynamics. Using a mixed-methods approach, the research integrates quantitative data—GDP growth, employment, infrastructure, and poverty reduction—with qualitative insights from government officials, community leaders, and residents. Between 2001 and 2020, Aceh received more than IDR 80 trillion (USD 5.5 billion) through SAF, enabling significant progress in infrastructure, education, and healthcare. Empirical evidence shows improvements in road connectivity, reduced travel time, increased school enrollment, lower maternal and infant mortality rates, and a decline in poverty from 22.5% in 2002 to 15.3% in 2020. Regression analysis indicates a positive correlation between SAF allocation and economic growth, averaging 5.2% during 2016–2020, while unemployment fell from 7.5% to 5.1% over the same period. Despite these achievements, governance challenges, fund mismanagement, and uneven allocation limit the full potential of SAF. Strengthening accountability mechanisms and enhancing transparency are essential for ensuring long-term sustainability. This study contributes to the literature on fiscal transfers and regional autonomy by highlighting the dual role of SAF as both an economic stimulus and a governance challenge. Future research should employ longitudinal and comparative designs to capture the broader implications of autonomy funds for regional development across Indonesia and other post-conflict settings.